Tracing Jewish Ancestry and Beyond—Exploring the Transformative Impact and Possibilities of the Documentation of Jewish Records Worldwide (DoJR) Project - Sallyann Sack; Amanda Kluveld (Genealogy)
This article analyses the transformative impact of the Documentation of Jewish Records Worldwide (DoJR) project, launched in 2017, on Jewish genealogy. Jewish genealogy, deeply rooted in centuries of tradition and cultural significance, transcends mere ancestral tracing, embodying a comprehensive exploration of Jewish history and heritage. The DoJR project represents a monumental shift in this field, aiming to compile a comprehensive, freely accessible online catalog, JCat, of every existing document of every Jew who ever lived. This endeavor reshapes our approach to Jewish genealogy and profoundly deepens our understanding of Jewish history. This article delves into the historical context of Jewish genealogy, tracing its evolution from ancient times through various challenges, including the Holocaust’s devastating impact on Jewish genealogical records. It highlights the pioneering efforts in the field and the modern advancements that have facilitated the growth of Jewish genealogy, including DNA testing and digital technologies.